A pilot single-institution predictive model to guide rib fracture management in elderly patients. Issue 5 (May 2015) - Gonzalez, Katherine W.; Ghneim, Mira H.; Kang, Francis; Jupiter, Daniel C.; Davis, Matthew L.; Regner, Justin L.
Abstract : BACKGROUND: Rib fractures (RFx) remain the most prevalent injury in an elderly population that will increase from 40 to 81 million for the next 30 years. We sought to create an accurate cost-effective algorithm to triage elderly patients with RFx that accounted for both frailty and trauma burden. METHODS: Retrospective analysis evaluated 400 patients older than 55 years with RFx admitted to a level 1 trauma center from 2007 to 2012. Comorbidities included chronic obstructive pulmonary disease, congestive heart failure, tobacco use, obesity, and nutrition and functional status. Trauma burden included RFx, tube thoracostomy, pulmonary contusions, and spine and extremity fractures. Patients with Glasgow Coma Scale scores lower than 13, thoracoabdominal surgery, or deaths from other causes were excluded. Comparative analysis used bivariate and logistic regression. Variables contributing to intubation (INT) and pneumonia (PNA) were then used to create a scoring system to predict the need for intensive care unit (ICU) admission. RESULTS: Six variables increased the risk for INT or PNA: chronic obstructive pulmonary disease, low albumin, assisted status, tube thoracostomy, Injury Severity Score, and RFx ( p < 0.05). These six variables and congestive heart failure (odds ratio, 1.9; p = 0.06) were used to create a predictive model with the following scores assigned respectively: 1.4, 1.1, 1, 0.9, 0.1(n), 0.1(n), and 0.6. A score lower than 3.7 had a sensitivity and specificity of 78.5% and 78.9%. The negative predictive value was 94.5% for INT or PNA, suggesting a low risk for ICU requirement. Ninety-two ICU admissions had a score lower than 3.7. Forty had no other indication for ICU admission aside from RFx. These patients had an average ICU length of stay of 1.7 days, resulting in an increased cost of $2, 200 per patient. CONCLUSION: A scoring system combining frailty and trauma burden may provide more accurate and cost-effective triage of the elderly trauma patient with RFx. Further prospective studies are required to verify our scoring system. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III.